Telecare service activity analysis using Big Data and Data Mining - Alfredo Moreno Muñoz; Juan Alfonso Lara Torralbo (Centro de Estudios Financieros, 2017)
In the current moment that we are living now, the use of Big Data is taken a strength and a very important relevance. The biggest companies of social sector and service sector are using Big Data technologies that allow to store and treat all the information that they have of users and, in a second way, the incorporation of the knowledge of the treatment of this information in the life of the users, in the way of improve the services offered and go to the next step in the relationship of customer/company. In telecare, with the IP technology in Telecare Unit, the communication between the unit and control centre will be done using internet instead of telephony cable. The companies will start to use these technologies to store all the information that the unit will send to the control center. With all this information, the companies will be able to discover patterns of user's behavior, detect some illnesses like, for example, alzheimer. The most important action that the companies will be able to have is to have more information related to the situation of all devices and sensors installed in user's home when the emergency alarm is raised.